2019
DOI: 10.1007/s10522-019-09818-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide exploratory study of monozygotic twins suggests differentially methylated regions to associate with hand grip strength

Abstract: Hand grip strength is a measure of muscular strength and is used to study age-related loss of physical capacity. In order to explore the biological mechanisms that influence hand grip strength variation, an epigenome-wide association study (EWAS) of hand grip strength in 672 middle-aged and elderly monozygotic twins (age 55–90 years) was performed, using both individual and twin pair level analyses, the latter controlling the influence of genetic variation. Moreover, as measurements of hand grip strength perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Given that AD is a typical disease of the nervous system that is associated with aging, we can reasonably predict the potential relationships between DLPFC and AD. On the basis of a monozygotic twin model, a study suggested that the demethylation of AMZ1 in DLPFC is associated with dyskinesia, another potential symptom of AD ( Soerensen et al, 2019 ). This report further confirmed the pathogenesis and downstream pathogenic regions of this methylation alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Given that AD is a typical disease of the nervous system that is associated with aging, we can reasonably predict the potential relationships between DLPFC and AD. On the basis of a monozygotic twin model, a study suggested that the demethylation of AMZ1 in DLPFC is associated with dyskinesia, another potential symptom of AD ( Soerensen et al, 2019 ). This report further confirmed the pathogenesis and downstream pathogenic regions of this methylation alteration.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation levels for the cg05429895 (TLR4) probe were extracted from an existing methylation data set. DNA extraction, sample preparation, data processing, and DNA methylation using the Infinium Human Methylation 450K BeadChip was performed as descripted in [62]. Complete data was obtained for 140 samples.…”
Section: Replication Of the Correlation Between Methylation Grade Of Tlr4 And Depressive Symptom Gradementioning
confidence: 99%
“…Complete data was obtained for 140 samples. Blood leukocyte cell subtypes were counted using a Coulter LH 750 Haematology as previously described [62]. Gene expression levels for probes in the gene TLR4 (2 probes) were extracted from an existing genome-wide transcriptome data set.…”
Section: Replication Of the Correlation Between Methylation Grade Of Tlr4 And Depressive Symptom Gradementioning
confidence: 99%
“…Anthropometric measures and whole blood samples were taken over the period from 2008 to 2011. Blood cell counts of 449 individuals were available and the blood cell counts of the other 9 individuals were imputed by the estimate CellCounts function in the R package minfi using DNA methylation data collected on the same blood samples [9,10].…”
Section: Samplesmentioning
confidence: 99%